Optimization of graphene in carbon black‐filled nitrile butadiene rubber: Constitutive modeling and verification using finite element analysis. Issue 5 (5th January 2020) - Goswami, Mohit; Mandloi, Bharat Singh; Kumar, Abhay; Sharma, Sujit; Ghorai, Sanjoy Kumar; Sarkar, Kajal; Chattopadhyay, Santanu
Abstract: Graphene nanoplatelet loading is varied in carbon black‐filled nitrile butadiene rubber (NBR) to form a hybrid system. The mechanical properties of the hybrid system are determined by performing tension and compression tests. It is found that graphene nanosheets are well dispersed possessing strong interfacial interaction with NBR and carbon black. There is an increment of 9% in tensile strength of the carbon black‐filled hybrid system with a graphene loading of 4 phr without hampering ultimate strain. Further addition of graphene resulted in degraded properties. Hyperelastic material models describing nonlinear mechanical behavior are fitted with experimental data to acquire material constants. Young's modulus is determined using various models, and a synergistic effect is observed with graphene loading of 4 phr. A comparison between experimental result and finite element analysis (FEA) result is presented for uniaxial tension and compression. Maximum principal stresses at break are also visualized with the help of FEA.